PEMIKIRAN SYEKH NAWAWI TENTANG PENDIDIKAN ISLAM DAN RELEVANSINYA DENGAN PENDIDIKAN MORAL DI ERA DISKRUPSI 5.0 - Muhammad Zaenuri, Maragustam (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2024)
Islamic education has a central role in the moral formation of mankind. The thoughts of Muslim figures such as Sheikh Nawawi Al-Bantani need to be presented in answering various challenges in the world of Islamic education, especially in moral education. This article discusses Sheikh Nawawi al-Bantani's thoughts on education in Islam and its relevance in the context of education in the era of disruption 5.0. According to Sheikh Nawawi, education plays a significant role in shaping human behavior, both spiritually and morally. Education, in the Islamic concept, includes three important terms: ta'lim, tarbiyah, and ta'dib, which reflect the transfer of knowledge, moral upbringing, and moral formation, respectively. This thinking is relevant to education in the 5.0 era, where technology must be used as a tool to shape character, not as a goal. The concept of ta'lim, which includes the transformation of knowledge and moral values, remains relevant in digital education. In addition, the concept of tarbiyah which emphasizes nurturing and moral growth, as well as ta'dib which focuses on the formation of morals, must still be considered in the midst of technological advances. Islamic education based on moral and spiritual values, as taught by Sheikh Nawawi, has great relevance for creating intellectually competent individuals with noble character in the midst of changing times.Keywords: Nawawi al-Bantani, Islamic Education, Era of Disruption 5.0.